Where are the gaps in improving maternal and child health in Mauritania? the case for contextualised interventions: a cross sectional study - VALLIERES, FRÉDÉRIQUE (My University, 2013)
Introduction: It is estimated that any progress made towards improving maternal and child health in Mauritania has likely stalled. A lack o f reliable and up - to - date data regarding maternal and chil d health indicators makes it difficult to identify current gaps and adapt international programmes to meet local needs Methods: Using secondary data collected as part of a baseline assessment for a maternal and child health programme being implemented in t wo health departments, we compared maternal and child health indicators across two different samples of pregnant women and children under - five in M ’ bagne and Guérou. Descriptive analyses were conducted using a Pearson ’ s Chi - Squared test, assuming a binomial distribution and a confidence level of alpha=0.05. Results: Our results indicated that there were marked regional differences in maternal and child health indicators between these two rural sites, with M ’ bagne generally performing better a cross a range of indicators including: immunisation rates, child registration, vitamin A supplementation, deworming, delivery in the presence of a skille d birth attendant, and post - natal care coverage. In Guérou we observed lower rates of fever, diarrhoea, and fast and difficult breathing among children under - five. Conclusion: Though socio - cultural differences may play a part in explaining some of these observed differences, these alone do not account for the observed differences in maternal and child healt h indicators. Context - specific activities to overcome barriers to care must be designed to address such rural regional differences if we are to see an improvement across maternal and child health indicators and accel erate progress towards MDGs 4 & 5 in Mau ritania.
PUBLISHED
Keywords: maternal child health Mauritania